A prospective randomized study on limits of colposcopy and histology: the skill of colposcopist and colposcopy-guided biopsy in diagnosis of cervical intraepithelial lesions. Issue 1 (December 2015) - Bifulco, Giuseppe; De Rosa, Nicoletta; Lavitola, Giada; Piccoli, Roberto; Bertrando, Alessandra; Natella, Valentina; Di Carlo, Costantino; Insabato, Luigi; Nappi, Carmine
Abstract Background The main objective of our study was to evaluate the colposcopist ability to correctly identify the worst area of a cervical lesion where biopsy should be performed; the secondary objective was to investigate the influence of the colposcopist skill in grading cervical preneoplastic lesions. Methods 296 patients referred for colposcopy were enrolled in a prospective study. All patients were randomized in two groups: in the first group, "senior group", the colposcopy was performed by an experienced colposcopist; in the second group, "junior group", the colposcopy was performed by a less experienced colposcopist. A detailed colposcopic description, including a grading of the lesion, was completed for each case. During the colposcopic exam patients underwent two direct biopsies; each biopsy was labeled with letter A (suspicious area with most severe grade) or B (suspicious area with less severe grade) according to the judgment of the colposcopist. An experienced pathologist reanalyzed the histological slides, after routine diagnosis. Results The senior group identify the worst area of the cervical lesion in statistical significant higher rates than junior group. Specimen A resulted representative of the higher-grade lesion (A > B) in 73.7 % (N = 28) in senior group and in 48.4 % (N = 15) in junior group; while in 26.3 % (N = 10) the higher-grade lesion corresponded to specimen B (A < B) in senior group and in 51.6 % (N = 16) in junior group (p < .05). Conclusion The ability of a colposcopist in grading cervical lesion depends on his experience.